2022
DOI: 10.1007/s10792-021-02171-8
|View full text |Cite
|
Sign up to set email alerts
|

Smart AMD prognosis through cellphone: an innovative localized AI-based prediction system for anti-VEGF treatment prognosis in nonagenarians and centenarians

Abstract: Background and ObjectiveAge-related macular-degeneration (AMD) is one of the most common reasons for blindness in the world today. The most common treatment for wet AMD is the intra-vitreal injections for inhibiting Vascular-Endothelial-Derived-Growth-Factor (VEGF). This treatment usually involves multiple injections and thus multiple clinic visits which not only causes increased cost on national health services but also causes exposure to the hospital environment which is sometimes high risk considering curre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
2
0
3
Order By: Relevance
“… 19 2023 ROP detection and grading Referral-warranted ROP (sensitivity ​= ​80.0%, specificity ​= ​59.3%) Treatment-requiring ROP (sensitivity ​= ​100.0%, specificity ​= ​58.6%) Fundus photographs taken by SBFI systems (the Make-In-India Retcam/Keeler Monocular Indirect Ophthalmoscope devices) ResNet18 / Qidwai et al. 18 2022 AMD prognosis prediction Accuracy >92.0% Measurements of baseline, changes in visual acuity and macular thickness after four months of treatment Adaptive neuro-fuzzy inference system Ophnosis AMD Nakahara et al. 21 2022 Glaucoma detection Glaucoma (AUC ​= ​0.842) Advanced glaucoma (AUC ​= ​0.900) Fundus photographs taken by an iPhone 8 with the D-Eye lens (D-EYE S.r.l., Padova, Italy) ResNet / Wu et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 2023 ROP detection and grading Referral-warranted ROP (sensitivity ​= ​80.0%, specificity ​= ​59.3%) Treatment-requiring ROP (sensitivity ​= ​100.0%, specificity ​= ​58.6%) Fundus photographs taken by SBFI systems (the Make-In-India Retcam/Keeler Monocular Indirect Ophthalmoscope devices) ResNet18 / Qidwai et al. 18 2022 AMD prognosis prediction Accuracy >92.0% Measurements of baseline, changes in visual acuity and macular thickness after four months of treatment Adaptive neuro-fuzzy inference system Ophnosis AMD Nakahara et al. 21 2022 Glaucoma detection Glaucoma (AUC ​= ​0.842) Advanced glaucoma (AUC ​= ​0.900) Fundus photographs taken by an iPhone 8 with the D-Eye lens (D-EYE S.r.l., Padova, Italy) ResNet / Wu et al.…”
Section: Resultsmentioning
confidence: 99%
“…explored a smart AI-based App based on adaptive neuro-fuzzy inference system to aid the clinician to visualize the progression of the patient and make better decisions related to the treatment. 18 The model had ultimately shown to have a high accuracy (92%) and works in near-real-time scenarios. Another study aimed to acquire a cost-effective alternative in the ROP telemedicine screening program by smartphone-based fundus imaging (SBFI) systems with AI and finally revealed that the two SBFI systems used in the ROP screening program were highly sensitive for treatment requiring-ROP.…”
Section: Resultsmentioning
confidence: 99%
“…Перспективність складання індивідуалізованого прогнозу на підставі визначення певних біомаркерів підтверджена можливістю оцінки ризику неефективності лікування пізньої ВМД інтравітреальними ін'єкціями інгібітору фактора росту судинного ендотелію (VEGF) [10]. Експрес-оцінка проводиться із застосуванням смартфону та оригінальної програми розрахунку гостроти зору та товщини макули через 8 і 12 місяців після лікування на підставі цих показників через 4 місяці.…”
Section: обговоренняunclassified
“…Модель має високу точність (>92%) і працює в режимі реального часу. Використання розробленої нами моделі (формула 1) також дозволяє на підставі невеликої кількості ознак спрогнозувати прогресію ВМД при різних початкових стадіях [10].…”
Section: обговоренняunclassified
See 1 more Smart Citation